Molecular divergence of secondary endosymbiont, Cardinium in Bemisia tabaci (Gennadius) and associates (Bangladesh Journal of Agricultural Research, 2015)
Whitefly, Bemisia tabaci (Hemiptera : Aleyrodidae) harbors numerous secondary endosymbionts, which are transmitted from mother to offspring by both horizontally and vertically, that have crucial role on host selection, biology, and evolution. Bacteria, Cardinium was identified in B. tabaci as well as in other whitefly population from many different countries by comparing 16S rDNA sequences. Cardinium were detected in all tested indigenous B. tabaci populations of Bangladesh, Myanmar, Nepal, and the Philippines as well as Q1 biotype of Korea. It was absent in B biotype of Korea and Q biotype of China. Cardinium was also detected in three out of five tested Aleurodicus dispersus population as well as in five out of seven Trialeurodes vaporariorum, whereas they were not detected in Tetraleurodes acaciae populatuion. In adition, Cardinium was detected in parasitoid Encarsia formosa attacking B. tabaci. Among the 19 whitefly populations from different countries, present studies identified four phylogenetic groups of Cardinium, thereby demonstrating the high diversity of this genus. Cardinium phylogeny suggests a correlation of geographical range with ecological variation at the species level.Bangladesh J. Agril. Res. 40(1): 121-135, March 2015